Cellular and Antibody Based Approaches for Pediatric Cancer Immunotherapy - Michael A. Huang; Deepa K. Krishnadas; Kenneth G. Lucas (Journal of Immunology Research)
Progress in the use of traditional chemotherapy and radiation-based strategies for the treatment of pediatric malignancies has plateaued in the past decade, particularly for patients with relapsing or therapy refractory disease. As a result, cellular and humoral immunotherapy approaches have been investigated for several childhood cancers. Several monoclonal antibodies are now FDA approved and commercially available, some of which are currently considered standard of practice. There are also several new cellular immunotherapy approaches under investigation, including chimeric antigen receptor (CAR) modified T cells, cancer vaccines and adjuvants, and natural killer (NK) cell therapies. In this review, we will discuss previous studies on pediatric cancer immunotherapy and new approaches that are currently being investigated in clinical trials.